A validation and acceptability study of cognitive testing using switch and eye-gaze control technologies for children with motor and speech impairments: A protocol paper - Karlsson, Petra; Honan, Ingrid; Warschausky, Seth; Kaufman, Jacqueline N.; Henry, Georgina; Stephenson, Candice; Webb, Annabel; McEwan, Alistair; Badawi, Nadia (Frontiers in Psychology, 2022)
Despite the importance of knowing the cognitive capabilities of children with neurodevelopmental conditions, less than one-third of children with cerebral palsy participate in standardized assessments. Globally, approximately 50% of people with cerebral palsy have an intellectual disability and there is significant risk for domain-specific cognitive impairments for the majority of people with cerebral palsy. However, standardized cognitive assessment tools are not accessible to many children with cerebral palsy, as they require manual manipulation of objects, verbal response and/or speeded response. As such, standardised assessment may result in an underestimation of abilities for children with significant motor and/or speech impairment. The overall aim of the project is to examine and compare the psychometric properties of standardised cognitive assessment tools that have been accommodated for use with either a switch device or eye-gaze control technologies. Specific aims are to: 1) Examine the psychometric properties of accommodated assessment tools by comparing the performance of typically developing children on six cognitive assessment tools administered via standardised versus accommodated (switch or eye-gaze control) administration; 2) Describe and compare the performance and user experience of children with cerebral palsy on six accommodated cognitive assessments administered via switch or eye-gaze control technologies. Secondary aims are to: 1) Describe the completion rates and time to complete assessments of participants in each group; 2) Within the group with cerebral palsy, examine the effects of condition-specific characteristics (type of cerebral palsy, functional levels, and pain) and demographics (age, socio-demographic) on participation. This protocol paper describes a two-phase validation and acceptability study that utilizes a mixed-model design. This study will collect concurrent data from 80 typically developing children and 40 children with cerebral palsy, who use switch or eye-gaze control technology as alternate access communication methods. The set of instruments will measure receptive vocabulary, fluid reasoning, sustained attention, vision perception, visuospatial working memory and executive functions. Data analyses will be conducted using SPSS v. 25 and R v 4.1.0. SPSS Sample Power 3 was used for power computation and allows for a 10% drop out rate. Quantitative descriptive statistics, measurement agreement data plotting, bivariate and multiple regressions analysis will be conducted.